Amphiregulin alleviated concanavalin A-induced acute liver injury via IL-22. (2nd September 2020) - Wu, Qili; Chen, Jingrou; Hu, Xiaoli; Zhu, Yinhong; Xie, Shujuan; Wu, Changyou; Pei, Zhong; Xiong, Shiqiu; Peng, Yanwen
Abstract: Objectives: Amphiregulin (Areg), a glycoprotein from the epidermal growth factor receptor (EGFR) ligand family, has a well-documented protective role against tissue injury; however, its effects on immune-mediated liver injury are still unclear. Here, we used a concanavalin A (ConA)-induced acute liver hepatitis model to explore the effects of Areg on immune-mediated acute liver injury. Materials and methods: Some C57BL/6 mice were administered ConA at a dose of 20 mg/kg (model mice), and some received 5 µg of Areg (treated mice). Then, their survival rates over 36 h were analyzed. After 5 h of treatment, liver function, hepatic histology, and apoptosis in liver tissue were investigated, and cytokine expression and neutrophil infiltration and activity in the liver were detected. Moreover, the protective effects of Areg were also evaluated without IL-22 in vivo . Results: Our results showed that Areg administration increased acute liver failure (ALF) mouse survival, restored liver function, and alleviated liver damage. Interestingly, Areg administration increased IL-22 production in hepatic T cells and upregulated IL-22 concentrations in the serum and liver, whereas IL-22 neutralization completely abolished the therapeutic effect of Areg. Meanwhile, Areg administration was concomitant with increased expression of the anti-apoptotic proteins Bcl-2 and Bcl-xL, which are important in the hepatoprotective mechanism of IL-22. Conclusions: Areg showed direct protective effects against ConA-induced acute liver injury, which suggests the potential therapeutic application of Areg in immune-mediated ALF.